Investigation of attitudes to the disease in rheumatic patients - Sargautytė, R.; Kočiūnas, R.; Krapavickaitė, R. (Psichologija, 1995)
Attitude to the diseases was studied in 429 patients with rheumatic diseases - rheumatoid arthritis, osteoarthrosis and systemic lupus erythematodes. The psychological differences among these three diagnostic group were revealed, the patients with systemic lupus erythematodes exhibiting an exceptional attitude to disease were investigated. The influence of various, clinical, psychological and social characteristics on this attitude was also studied. Significant findings (with significance level 0,05) were obtained regarding age, sex, activity of disease and level of education. The level of neurotic complaints was not related to the type of attitude. The most stable occurred to be neurasthenic and dysphoric reactions, the least – harmonious and apathic, as measured repeatedly after a considerable period of time.
Keywords: rheumatic patients; attitudes to the disease